Percutaneous Transforaminal Endoscopic Decompression for Lumbar Lateral Recess Stenosis - Lu, Hui-gen; Pan, Xue-kang; Hu, Min-jie; Zhang, Jian-qiao; Sheng, Jian-ming; Chen, Bao; Zhou, Xiao; Yu, Yefeng; Hu, Xu-qi (Frontiers in Surgery, 2021)
Objective: The aim of this study was to evaluate the treatment efficacy of lateral spinal stenosis through the decompression of the nerve root under a multiple planar endoscope. Methods: From January 2017 to March 2019, 52 patients with lumbar spinal stenosis or lumbar spinal stenosis combined with intervertebral disc herniation had been treated via transforaminal approach spinal endoscopy. Our study retrospectively analyzed the treatment outcome. All patients experienced complications with different degrees of facet joint hyperplasia and ligamentum flavum hyperplasia and hypertrophy. Some patients suffered disc herniation. All patients were treated with percutaneous transforaminal approach multiple planar endoscopic decompression. The visual analogue scale (VAS) and the Oswestry Disability Index (ODI) were compared before and after the operation, as were the horizontal foramen areas of the medial margins of the upper and lower pedicles of the vertebral arch. The treatment effectiveness was evaluated. Results: VAS and ODI scores were significantly improved at postoperative three days, three months, six months, and the last follow-up (P<0.05). The area of the intervertebral foramen was 422.5±159.2 mm2 preoperatively and 890.8±367.7 mm2 postoperatively, the difference was statistically significant (P<0.05). Conclusion: Percutaneous transforaminal approach multiple planar endoscopic decompression could achieve an accurate and effective decompression of the lumbar lateral spinal canal. This procedure has good short-term effects, and is especially suitable for elderly patients.